2019
DOI: 10.1590/s1677-5538.ibju.2019.0121
|View full text |Cite
|
Sign up to set email alerts
|

Which of available selective serotonin reuptake inhibitors (SSRIs) is more effective in treatment of premature ejaculation? A randomized clinical trial

Abstract: Purpose: To compare the effi cacy and safety of available selective serotonin reuptake inhibitors (SSRIs) in order to fi nd the most effective drug with the least number of side effects in treatment of premature ejaculation (PE). Materials and Methods: This study was a randomized clinical trial. Four hundred and eighty patients with PE in the 4 groups referred to Imam Reza hospital Tehran, Iran from July 2018 to February 2019 were enrolled in the study. The patients received sertraline 50mg, fl uoxetine 20mg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Twenty‐four articles (Abdel‐Hamid et al, 2001; Abu El‐Hamd & Abdelhamed, 2018; Alghobary et al, 2010; Arafa & Shamloul, 2007; Gameel et al, 2013; Gong et al, 2011; Hamidi‐Madani et al, 2018; Homayuonfar et al, 2018; Kirecci, Simsek, Gurbuz, et al, 2014; Kirecci, Simsek, Yuksel, et al, 2014; McMahon & Touma, 1999; Moudi & Kasaeeyan, 2016; Otunctemur et al, 2014; Ozcan et al, 2015; Polat et al, 2015; Safarinejad, 2006; Salonia et al, 2002; Siroosbakht et al, 2019; Sunay et al, 2011; Ur Rehman et al, 2020; Waldinger, Hengeveld, & Zwinderman, 1994, 1997; Waldinger et al, 2004; Wang et al, 2007) with 25 RCTs including 2,308 patients were used to evaluate the efficacy and safety of “on‐demand” and “daily” paroxetine in treating PE. A flow diagram of selection process was shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐four articles (Abdel‐Hamid et al, 2001; Abu El‐Hamd & Abdelhamed, 2018; Alghobary et al, 2010; Arafa & Shamloul, 2007; Gameel et al, 2013; Gong et al, 2011; Hamidi‐Madani et al, 2018; Homayuonfar et al, 2018; Kirecci, Simsek, Gurbuz, et al, 2014; Kirecci, Simsek, Yuksel, et al, 2014; McMahon & Touma, 1999; Moudi & Kasaeeyan, 2016; Otunctemur et al, 2014; Ozcan et al, 2015; Polat et al, 2015; Safarinejad, 2006; Salonia et al, 2002; Siroosbakht et al, 2019; Sunay et al, 2011; Ur Rehman et al, 2020; Waldinger, Hengeveld, & Zwinderman, 1994, 1997; Waldinger et al, 2004; Wang et al, 2007) with 25 RCTs including 2,308 patients were used to evaluate the efficacy and safety of “on‐demand” and “daily” paroxetine in treating PE. A flow diagram of selection process was shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Partner sexual satisfaction and IIEF rate were greater with 90 mg fluoxetine, but no statistical difference was found. Siroosbakht et al, 2019 [ 151 ] RCT Fluoxetine 20 mg Paroxetine 20 mg Citalopram 20 mg Sertraline 50 mg 8 weeks 480 Mean (SD) IELT before, 4 and 8 weeks after treatment in four groups was: sertraline 69.4 (54.3), 353.5 (190.4), 376.3 (143.5) s; fluoxetine 75.5 (64.3), 255.4 (168.2), 314.8 (190.4) s; paroxetine 71.5 (69.1), 320.7 (198.3), 379.9 (154.3) s; citalopram 90.39 (79.3), 279.9 (192.1), 282.5 (171.1) s, respectively. IELT significantly increased in all groups ( P < 0.05), but there was no significant difference between the groups ( P = 0.75).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological interventions (Table 3) [24,26,27,32,47,48,[50][51][52][55][56][57][58][59]66,67,72,73,[76][77][78][79]81,[84][85][86][87]89,90,116,[151][152][153][154][155][156][157][158][159][160][161][162][163]…”
Section: The Effectiveness Of the Start/stop And Squeeze Techniquesunclassified
“…In fact, fluoxetine and paroxetine (20 mg) is effective in the management of premature ejaculation. 2,3 Moreover, the authors reported 32 patients sexual dysfunction were treated with mirtazapine, while mirtazapine does not cause sexual dysfunction as other selective serotonin reuptake inhibitors (SSRIs). 4 In addition, venlafaxine, a norepinephrine-serotonin reuptake inhibitor, was reported as an effective drug in the management of premature ejaculation.…”
Section: Prevalence Of Antidepressant-induced Sexual Dysfunction Among Psychiatric Outpatients Attending a Tertiary Care Hospitalmentioning
confidence: 99%